PENGARUH MODEL PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN BERFIKIR KREATIF DAN HASIL BELAJAR SISWA - Benny Sofyan Samosir; Lisna Agustina; Tua Hudyansah (Jurnal Karya Pendidikan Matematika, 2019)
The low ability of creative thinking and student learning outcomes becomes the discussion of this study. To overcome this problem, in this study applied the Contextual Learning Model. the purpose of this research is useful to answer whether there is an increase in creative thinking skills between contextual learning models and conventional learning models then to find out whether there are differences in mathematics learning outcomes in a positive direction through this contextual learning model. The type of research used in this research is experimental research where the population of this study is all students of Class X Padangsidimpuan 6 High School. Data analysis using the t-test statistical test. Based on the results of the calculation of the hypothesis test the value of t count > t table or 2.007 > 1.667 (with α 0.05), so Ha is accepted and H0 is rejected. This means that there is a significant increase in creative thinking skills in the experimental class compared to in the control class.